Applying a decision tree framework in support of an ecosystem approach to fisheries: IndiSeas indicators in the North Sea. (9th December 2017) - Lockerbie, Emma M; Lynam, Christopher P; Shannon, Lynne J; Jarre, Astrid; ,
Abstract: As one of the most economically important marine ecosystems, the North Sea has been impacted by numerous anthropogenic activities. A move towards an ecosystem approach to fisheries is key in developing sustainable fisheries in marine ecosystems. The application of a previously tested decision tree framework that employs a suite of indicators suggested in the IndiSeas project with additional indicators of environmental variability has been used in this study. Trends in indicators were used to identify ecosystem trends across three periods: 1983–1992, 1993–2003, and 2004–2010. A score-based approach was adopted, assigning scores to indicators based on direction and significance of trends. Ecological indicator scores were adjusted to account for impacts of fishing and environmental variability. Overall ecosystem scores assigned the ecosystem into one of five possible categories: improving, possibly improving, no improvement/deterioration, possibly deteriorating or deteriorating. Results indicated no improvement or deterioration over Period 1 (1983–1992); whereas Periods 2 (1993–2003) and 3 (2004–2010) showed a possible improvement of the ecosystem. Use of a structured decision tree framework, including extensive literature reviews and knowledge from ecosystem experts, allows the determination of ecosystem trends in a way consistent with ecological theory.